A case study of evidence for showing 'no net loss' of bird biodiversity in a development project. (15th June 2015) - Murata, Natsuki; Feest, Alan
Abstract Given the development of global pressures on habitats and biodiversity, it is important that developments are accompanied with a compensation element leading to 'no net loss'. We show how (using a standardised sampling process) a statistical assessment of the biodiversity quality of the target organisms (birds) in a compensatory provision can be shown to be a compensation or not. We used the example of the Cardiff Bay Barrage (Wales) where a bay was inundated and compensation site at Newport Gwent Levels (Wales) created. Bird data for the Cardiff Bay prior to the inundation and for Newport following inundation of Cardiff Bay were analysed to create a series of biodiversity quality indices and these were compared statistically. The analysis showed the compensation habitat was better than the original. Results were poor for Dunlin and Redshank, already subject to regional decline in the Severn Estuary and estuaries in NW Europe.